Performance of vertical cantilever with tip mass as MTMDs in controlling response of structures for ground motions - Sajith, A.S; Pillai, T.M. Madhavan; Ameen, Mohammed; Thomas, Sobin (Journal of Structural Engineering, 2024)
The performance of vertical cantilever with tip mass used as Multiple Tuned Mass Dampers (MTMDs) in controlling response of structures is discussed in this paper. The study involves both experimentation and numerical simulations. Experiments are done on small scale elastic building models through a uni-axial shake table. Numerical simulation of the same is done in MATLAB. The effectiveness of the control device is worked out based on the reduction in response of the top storey displacement of the building models. Results for harmonic base excitation of the models are presented in this study. The findings reveal that this could be a simple and effective solution for response mitigation of structures.